Ghulam Ahmad Parvez on issues concerning women: A critical analysis - Osmani, Noor Mohammad (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2012)
Ghulam Ahmad Parvez (1903-1985) provides a modern interpretation of Islam which in many cases contradicts the tenets and teachings of Islam. He rejects the authority of the hadith (sayings) of the Prophet (SAW). His modernist approach covers a wide range of issues including women. His views on women largely contradict the Islamic texts from the Qur’an and Sunnah. Relying primarily upon his writings in various magazines and also in his magnum opus Tafsir Matalib al-Furqan, this paper analyzes his views from an objective critical perspective based upon the Qur’an, the Sunnah and the writings of the prominent scholars. It has been observed that by way of rejecting Sunnah as the authority in Shari`ah, Parvez rejects many issues of Shari’ah which are accepted by majority of Muslim scholars.